IMPLEMENTATION OF EDUCATIONAL SUPERVISION TO IMPROVE TEACHER PERFORMANCE: A COMPARATIVE STUDY AT INDONESIAN AND PAKISTANI SCHOOL - Wulandari, Tria Ayu; Yaseen, Muhammad; Wafi, Abdul; Nurhadi, Ali; Mubah , Hilmi Qosim; Ratnawati, Rinta (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2023)
Educational supervision should be conducted for various reasons one of them is to improve teachers’ perfomance as well as to improve students’ learning and quality of education. This is a comparative study of Indonesian and Pakistani school; Madrasah Ummul Quro At-Tarbawiyah Indonesia and Dar-e-Arqam School Bawalpur Punjab Pakistan. There are three research focuses, namely (1) how is the educational supervision implemented in those schools? (2) how effective is the implemenetation of educational supervision in those schools? (3) what are the problems and solutions of the implementation of the educational supervision. This study adopted a descriptive qualitative approach with interviews, observation and documentation as data collection. The results show that the director of Madrasah at Madrasah Ummul Quro At-Tarbawiyah Indonesia implemented educational supervision by using group technique through 3 activities- a monthly meetings, weekly meetings and trainings. through these forms of activity, the results are obtained in the form of positive changes from the teachers which also indirectly affect the effectiveness of the learning activities carried out so as to obtain optimal results through students’ achievements. The obstacles faced are related to the teacher's internal condition so that the alternative is by giving summons, providing motivation, and the final action is in the form of teacher transfers. Menwhile, in Dar-e-Arqam School Pakistan, head office monitoring visits implemented the supervision by monitoring visit and training session (physical and online), reports, and performance conducted monthly and in the end of semester. The head office then made the decision and guidelline for the improvement.